Implementation of a Desktop-Based Sales Information System Using the Waterfall Method - Rangkuti, Haris Munandar; Marbun, Nasib (Information Technology and Science (ITScience), 2025)
In today's digital era, information technology has become an integral part of various aspects of life. One of the many utilizations of information technology products is a desktop-based information system. The purpose of this research is to implement a desktop-based sales information system to solve the problem of data redundancy, calculation errors in sales transactions, and excessive use of time in the process of managing sales data in the Culinary business field because it still utilizes conventional methods. The sales information system developed in this study was built using the Visual Basic Net programming language. Visual basic net is an object-oriented programming language designed to build a variety of windows applications. The database used in the sales information system in this research is Microsoft Access. The collection methods used to obtain the required research data include observation, interviews, and literature studies. The system development method that the author uses to build a desktop-based sales information system in this research is the Waterfall method. The results of this study are in the form of a desktop-based sales information system equipped with various features to make it easier for users to systematically process sales data in the culinary business field. The desktop-based sales information system produced in this research allows faster and more accurate data management compared to conventional methods.